Trends in pre-operative needle biopsy use in invasive breast cancer diagnosis: a Dutch nationwide population study. (1st December 2020) - Bulte, J. P.; Simsek, D.; Bult, P.; de Wilt, J. H. W.; Strobbe, L. J. A.
Abstract: Introduction: In recent decades, the use of pre-operative needle biopsy for breast cancer diagnosis has shifted. There is also an increased demand for availability of predictive factors. This study aims to quantify these changes. Material and methods: From the Dutch nationwide pathology database (PALGA), all reports on breast cancer for five periods of 3 months between 1996 and 2016 were retrieved. Reports were categorised using automatic recognition of keywords. Classification was checked manually for the first 200 reports per period. The first 100 resected cases in each period underwent detailed investigation. Results: For automatic analysis 34, 639 reports were retrieved. Accuracy was 98% compared to manual assessment. Fine needle aspiration cytology (FNAC) decreased from 77% (1996) to 58% (2001), 34% (2006), 25% (2011), and 17% (2016). For detailed assessment, 498 cases were analysed. Diagnostic surgical excision decreased from 24% in 1996 to 3% in 2016, cases with only cytology from 65% to 1%, respectively. Cytology and core needle biopsy (CNB) were combined in 21% of cases in 2016. Pre-operative availability of ER status increased from 3% in 1996 to 36% in 2006 and 78% in 2016 (as compared to 47%, 92%, and 97% for post-operative availability, respectively) and for HER2 status from 0% to 13% and 66% (as compared to 1%, 89%, and 96% for post-operative availability, respectively). Conclusion: Results suggest that nationwide, clinics prioritise reliability and availability of ER and HER2 status, replacing FNAC by CNB. However, for optimal treatment planning for all patients, availability of pre-operative receptor status warrants further improvement.